Elemental analysis, extraction conditions, and brine shrimp toxicity of defatted Hylocereus polyrhizus seed - Gani, Siti Salwa Abd; Zulkifli, Siti Atikah; Zaidan, Uswatun Hasanah; Misran, Azizah; Mat Radzi, Salina (Malaysian Institute of Chemistry, 2024)
Extracts prepared from Hylocereus polyrhizus have received attention in pharmacological research due to their potent anti-inflammatory, antioxidant, anti-cancer, anti-diabetic, and anti-microbial effects. This current study aims to determine the level of multi-element contents, the effect of different extraction conditions on the total amount of polyphenolic content, the antioxidant potential, and the toxicity of the Defatted H. polyrhizus Seed Extract (DHPSE). The phenolic content was evaluated through Total Phenolic Content (TPC) and Total Flavonoid Content (TFC), while the antioxidant levels were measured through 2,2-diphenyl -1- picrylhydrazyl (DPPH) radical scavenging activity. The toxicity of the DHPSE extract was assessed through a brine shrimp lethality assay. The DHPSE exhibited the presence of potassium (K), calcium (Ca), magnesium (Mg), sodium (Na), iron (Fe), zinc (Zn), copper (Cu), manganese (Mn), aluminum (Al), chromium (Cr), nickel (Ni), lead (Pb), cobalt (Co), and selenium (Se). The current study also revealed that all the various extracting conditions of DHPSE possessed a significant influence (p < 0.05) on the antioxidant capacity and polyphenolic content and presented no toxicity effect. The optimized conditions determined for ethanol concentration, extraction time, and temperature were 80%, 60 minutes, and 80℃, respectively. These ideal parameters gave 120.33 mg GAE/g sample and 10.76 mg QE/g sample, respectively, with 92% inhibition of DPPH scavenging. Therefore, these findings provide valuable insight for the future utilization of defatted H. polyrhizus seed.